Pengaruh Pemberdayaan Karyawan dan Kepuasan Kerja Terhadap Produktivitas Perusahaan di Toyota Auto2000 Tanjung Api-Api Palembang - Muhammad Tio Septa Syafril (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of employee empowerment and job satisfaction on company productivity at Toyota Auto 2000 Tanjung Api-Api Palembang. Primary data used in this study were obtained from a questionnaire filled out by 178 respondents. Then the data is processed using multiple linear regression analysis method. The results indicates that employee empowerment (X1) and job satisfaction (X2) had a significant positive effect on company productivity (Y). This research is expected to become literature on the topic of employee empowerment, job satisfaction and company productivity.